Poverty and Inequality in the Age of Globalization - Tiberi, Mario (TNEU, 2007)
The paper examines the recent performance of the world economy using the two fundamental criteria of efficiency and equity. The common term of glob- alization is applied showing, on the one side, its multidimensional aspect, while on the other, its extension to different historical periods. Then the phase of the Pax Britannica is recalled, when the rules of the game essentially were the gold standard and free trade. It is compared with the contemporary Pax Americana governed by the neo-liberal Washington Consen- sus, which has tried to harmonize the behaviour of the main private and public actors of the recent economic evolution: transnational companies, international financial intermediaries, nation states, regional and international organizations. The «trickling down approach», which has inspired this Consensus, sug- gests that efficiency can drive equity to some extent, relying on market mecha- nisms above all. The limits of this point of view are shown, considering the em- pirical evidence, where the general picture of a growing world economy is ac- companied by some critical remarks in terms both of inequalities between and within countries, and frequent signs of instability. A new way of thinking is, therefore, emerging at all levels, to suggest a strong and direct link between equity and efficiency; it asks for more interven- tionism, especially in the institutional field. In line with this trend, the paper ar-gues in favour of creation of the World Labour Organization, more democracy and transparency in the existing international organizations, more regionalization than globalization.
Keywords: Equity and efficiency; globalization; inequalities between and within countries; nation states; Pax Britannica and Pax Americana; regional and international organizations; regionalization; transnational companies and international financial intermediaries; Washington Consensus and the «trickling down approach»; World Labour Organization